Revenue Recycling and the Welfare Effects of Road Pricing - Parry, Ian W. H., 1965- 1965- (The World Bank, 1999)
December 1999 - The presence of preexisting tax distortions, and the form of revenue recycling, can crucially affect the size - and possibly even the sign - of the welfare effect of road pricing schemes. The efficiency gains from recycling congestion tax revenues in other tax reductions can amount to several times the Pigouvian welfare gains from congestion reduction. Parry and Bento explore the interactions between taxes on work-related traffic congestion and preexisting distortionary taxes in the labor market. A congestion tax raises the overall costs of commuting to work and discourages labor force participation at the margin when revenues are returned in lump-sum transfers. The resulting efficiency loss in the labor market can be larger than the Pigouvian efficiency gains from internalizing the congestion externality. By contrast, if congestion tax revenues are used to reduce labor taxes, the net impact on the labor supply is positive and the efficiency gain in the labor market can raise the overall welfare gains of the congestion tax by as much as 100 percent. Recycling congestion tax revenues in public transit subsidies produces a positive, but smaller, impact on the labor supply. In short, Parry and Bento's results indicate that the presence of preexisting tax distortions, and the form of revenue recycling, can crucially affect the size - and possibly even the sign - of the welfare effect of road pricing schemes. The efficiency gains from recycling congestion tax revenues in other tax reductions can amount to several times the Pigouvian welfare gains from congestion reduction. This paper - a product of Infrastructure and Environment, Development Research Group - is part of a larger effort in the group to study the cost-effectiveness of alternative transport policies.